Iskanje novih evropskih identitet: uganka globalnih identitet - Žagar, Mitja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2002)
The EU (Eastern) enlargement brings several issues to the top of the political agenda both in the individual member states and candidate countries and at the level of the EU. Among those important issues, which will be discussed also at the EU (Constitutional) Convention, are the institutional reforms of the EU and political systems within the individual member states and candidate countries and an (over)arching topic of the European identity. Discussion on the institutional reforms will include, among othersČ the eminent needs for operative and effective EU common institutions (government) overcoming the existing democratic deficit and (re)definition of ever changing relations and balances between member states and the EU, including the distribution of powers and competencies different views regarding the future development and nature of the EU, including the issues of supranationality (even federalism) and national sovereignty, and the division of competences between the EU and member states etc. I expect that the existence and formation of ("new") European identity - or better, European identities - will also be addressed in this context. The plurality of distinct European identities is conditioned by the existing diversities (including specific historic developments) in Europe. However, these distinct European identities share several common elements. The development of new common European identities is only possible if they include and can accommodate diverse local, regional, ethnic, national, religious, etc. identities that exist in Europe. New common European identities have to and can exist only simultaneously and in coexistence with other identities presentin Europe. These new identities should be structured and multi-layered identities, new qualities with characteristics of their own. They have to complement the traditional national identities and patriotism and develop democratic supranational patriotism, which is only possible if the democratic legitimacy of the European integration is ensured. I would argue that the development of new common European identities is also an important precondition for a successful EU institutional reform.
Keywords: identiteta; narodna identiteta; social psychology; socialna psihologija; mednarodne integracije; Europe; Evropa; Evropska unija; European Union